Penerapan Metode Tutor Sebaya untuk Meningkatkan Sikap Tasamuh dan Hasil Belajar PAI - Dinna Muthia Atsa; Ahmad Khoiri; Siti Lailliyah (JOURNAL SAINS STUDENT RESEARCH, 2025)
Tolerance, or tasamuh, is a fundamental value in Islamic religious education that should be cultivated from an early age within the school setting. Nevertheless, many students still demonstrate a lack of mutual respect during the learning process. This research aims to examine the influence of the Peer Tutoring instructional method on students’ tolerance attitudes and learning achievements in Islamic Religious Education among tenth-grade students at SMA Negeri 1 Selomerto. The study employed a quantitative approach with a quasi-experimental design. Data were gathered through observations, questionnaires, and achievement tests, then analyzed using t-tests and N-Gain calculations. The results showed a statistically significant difference between the experimental group that implemented Peer Tutoring and the control group, with a t-score of -7.621 and a p-value of less than 0.001, along with an average increase of 22.250 points in learning outcomes. Regarding tolerance attitudes, a significant distinction was also identified, marked by a t-value of -18.695 and a p-value below 0.001, with a mean difference of 13.500 points. The N-Gain analysis revealed a moderate level of improvement, with the experimental group scoring 0.55 and the control group scoring 0.49. These findings indicate that the Peer Tutoring method is an effective strategy for improving both students’ academic performance and their attitude of tolerance, and it can serve as a viable alternative for instructional practices in Islamic Religious Education.